Pragmatics of the Development of Personal Identity in Adolescents in the Latin American Context - Tapia Balladares, Javier (2017)
The present work proposes a pragmatic perspective of the development of personal identity. Such perspective is based on a unifying vision that incorporates the contribution of communicative pragmatics and becomes aware of the contribution of semiotics to psychology, without leaving aside the eriksonian point of view and other significant contributions in the field. The article defines identity in adolescence from a development approach, and adopts a systemic perspective concerning the insertion of adolescents in their context of formation as individuals. It then proposes a way to understand identity from a pragmatic-communicative perspective. Finally, it introduces two communicative use contexts from which personal identity can emerge, showing the importance of communication and language in the formation and development of identity.